2012
DOI: 10.1016/j.visres.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of isoleucine for threonine at position 190 of S-opsin causes S-cone-function abnormalities

Abstract: Five mutations in the S-cone-opsin gene (OPN1SW) that give rise to different single amino-acid substitutions (L56P, G79R, S214P, P264S, R283Q) are known to be associated with tritan color-vision deficiency. Here we report a sixth OPN1SW mutation (T190I) and the associated color vision phenotype. S-opsin genotyping and clinical evaluation of color vision were performed on affected and unaffected family members and normal controls. Chromatic contrast was tested at different levels of retinal illuminance. Affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The genetically-confirmed protan carrier control had an estimate of 39% L cones, which was lower than any of the female normal trichromats. She was also heterozygous for the S-opsin mutation Tl 901, which causes abnormal S-cone function ( Baraas, Hagen, Dees, & Neitz, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genetically-confirmed protan carrier control had an estimate of 39% L cones, which was lower than any of the female normal trichromats. She was also heterozygous for the S-opsin mutation Tl 901, which causes abnormal S-cone function ( Baraas, Hagen, Dees, & Neitz, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, tritan scores of the elderly did not indicate tritanopia, at least when compared with the tritan vector length (at the limit of 1000) observed for one congenital tritanope, not included in this study, with a confirmed P264S mutation of the S-cone opsin gene on chromosome 7 [42,43]. For other older subjects with high tritan vectors, we cannot exclude the possibility of incomplete penetrance of an S-cone mutation that could result in milder tritan deficiencies [44,45], although this is unlikely in view of the low prevalence. Older observers often have acquired deficiency of color vision secondary to retinal or optic nerve disease affecting tritan discrimination [46,47]; however, retinal diseases were exclusion criteria for participation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The normal controls and 16 of the participants with aniridia (age 11–66 years, logMAR 0.00–0.90) were tested with the CCT Trivector test following standard procedures. 46 , 47 The test was performed binocularly and took 3 to 4 minutes to complete. Participants were tested twice, and average thresholds were used for analysis.…”
Section: Methodsmentioning
confidence: 99%